Lighting people : A photographer's reference - Vanon, Rossella (London, Octopus Publishing Group, 2016)
This comprehensive guide includes a complete introduction to gear and technique, and a full lighting reference featuring models of different ethnicity lit from many different angles, so you can plan a lighting concept without moving any gear.
Includes resources and index.